E - Sports: a legitimate sport? - Cerqueira, Matheus (2020)
Currently, our society is facing an increase in the levels of physical inactivity in the world population, especially an increase in screen time, causing potential adverse effects in the short and long term to health (Stiglic & Viner, 2019; Domingues‐Montanari, 2017). Several institutions, such as the World Health Organization (WHO), American College of Sports Medicine (ACSM), and National Institute for Health and Care Excellence (NICE), recognize the importance of physical exercise as a potential tool against the risks associated with sedentary behavior (Piercy et al., 2018). And within that context, a question must be asked; can screen time be considered time spent on sports?(…)